2014
DOI: 10.1186/1477-7819-12-199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and hypoxic marker expression of primary sinonasal and laryngeal small-cell neuroendocrine carcinoma: a small case series

Abstract: BackgroundSmall-cell neuroendocrine carcinoma (SCNEC) of the head and neck is rare. The prognosis of SCNEC in the nasal cavity and larynx is poor. The aim of this study was to investigate the clinicopathological features of nasal and laryngeal SCNEC and to determine the expression of HIF-1α, GLUT-1, PI3K, and p-Akt in SCNEC.MethodsBetween 2003 and 2012, 10 consecutive patients with histologically demonstrated nasal and laryngeal SCNEC were enrolled. Clinicopathological materials and follow-up data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Our previous studies showed high expression of GLUT-1 in head and neck cancer [54], ceruminous adenoma [55], head and neck inflammatory myofibroblastic tumors [56], and nasal and laryngeal neuroendocrine carcinoma [57]. Li detected GLUT-1 expression in all 25 cases of head and neck cancer examined, with expression found mainly in the cell membrane.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous studies showed high expression of GLUT-1 in head and neck cancer [54], ceruminous adenoma [55], head and neck inflammatory myofibroblastic tumors [56], and nasal and laryngeal neuroendocrine carcinoma [57]. Li detected GLUT-1 expression in all 25 cases of head and neck cancer examined, with expression found mainly in the cell membrane.…”
Section: Introductionmentioning
confidence: 98%
“…In general, the tumors are clinically large and destructive, frequently accompanied by tumor necrosis (Figure 8), showing bone destruction, perineural invasion, and lymphovascular invasion. 52,80,85 The tumors grow in multiple patterns, including sheets, nests, lobules (Figure 8), ribbons, festoons, and trabeculae, occasionally showing rosettes or palisading. The cells are small to medium, with nuclear molding, apoptosis, prominent crush artifact, and cannibalism, with a high mitotic index (410/10 high power fields) including atypical forms.…”
Section: Nut Carcinoma (Squamous Cell Carcinoma)mentioning
confidence: 99%
“…Glut-1, as an important carrier of glucose uptake and a major protein involved in the transport of glucose, plays a key role in maintaining the homeostasis of the body [9]. It has been reported that Glut-1 transporters are expressed at higher levels in human solid cancer cells compared to their normal counterparts [10][11][12]. Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18.…”
Section: Introductionmentioning
confidence: 99%